Pengaruh Pendidikan Moral Terhadap Kepatuhan Kepada Orang Tua dan Guru di Sekolah SDN 1 Bojonegara - Fadiyatun Nufus; Desty Endrawati Subroto; Nailah Nahdzah Jayan; Nadzifah Nurjannah; Annisa Alifiyani (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This research aims to examine the relationship between moral education and obedience to parents and teachers in elementary schools.Through literature review and quantitative analysis, this research reveals that the influence of moral education on obedience to parents and teachers at school has a significant impact on students' ethics and actions in participating in social activities.In this regard, the challenge in the Indonesian education sector is to improve the quality of learning to produce graduates who are competitive, able to adapt to changes, and creative in solving the challenges they face.The process of moral education needs to be nurtured from an early age and should be maximized starting from elementary school.The goal of moral education in elementary school is to shape students' character to be good, ethical, responsible, and capable of making decisions based on positive values, as well as living harmoniously in society.This is done so that students have personal and social competencies, and become good citizens.The function of moral education in schools is to shape students' character to be integrity-driven, socially responsible, and ethical.Moral education also helps students understand the importance of moral values in everyday life.